Broadband (22–40 GHz) multistage MMIC low‐noise amplifier. Issue 4 (April 2016) - Gao, Xingzhen; Yang, Shuang; Gu, Jianzhong; Wang, Wei; Sun, Xiaowei
ABSTRACT: In this article, a wideband (22–40 GHz) four‐stage monolithic microwave integrated circuit low noise amplifier has been presented, which was fabricated in WIN 0.15 um pseudomorphic high electron‐mobility transistor technology. The source inductor and interstage mismatching methods were used to realize both low noise and flatten gain simultaneously in wideband. The designed LNA has achieved a gain of 22 ± 1 dB and a noise figure of less than 3 dB from 22 to 40 GHz. The chip size was 2 × 1 mm 2, which can be used in active phased‐array receiver modules, millimeter wave imaging, broadband wireless communication systems, and 24‐GHz short‐range sensors. In addition the LNA was worked with only one supply power, which was realized by four self ‐bias resistances. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:956–959, 2016